Early Family Intervention for Youth at Risk for Bipolar Disorder: Psychosocial and Neural Mediators of Outcome - Miklowitz, David J.; Weintraub, Marc J.; Walshaw, Patricia D.; Schneck, Christopher D.; Chang, Kiki D.; Merranko, John; Garrett, Amy S.; Singh, Manpreet K. (Current Neuropharmacology, 2023)
Background: The impairing neurodevelopmental course of bipolar disorder (BD) suggests the importance of early intervention for youth in the beginning phases of the illness. Objective: We report the results of a 3-site randomized trial of family-focused therapy for youth at high-risk (FFT-HR) for BD, and explore psychosocial and neuroimaging variables as mediators of treatment effects. Methods: High-risk youth (<18 years) with major depressive disorder or other specified BD, active mood symptoms, and a family history of BD were randomly assigned to 4 months of FFT-HR (psychoeducation, communication and problem-solving skills training) or 4 months of enhanced care psychoeducation. Adjunctive pharmacotherapy was provided by study psychiatrists. Neuroimaging scans were conducted before and after psychosocial treatments in eligible participants. Independent evaluators interviewed participants every 4-6 months over 1-4 years regarding symptomatic outcomes. Results: Among 127 youth (mean 13.2 ± 2.6 years) over a median of 98 weeks, FFT-HR was associated with longer intervals prior to new mood episodes and lower levels of suicidal ideation than enhanced care. Reductions in perceived family conflict mediated the effects of psychosocial interventions on the course of mood symptoms. Among 34 participants with pre-/post-treatment fMRI scans, youth in FFT-HR had (a) stronger resting state connectivity between ventrolateral PFC and anterior default mode network, and (b) increased activity of dorsolateral and medial PFC in emotion processing and problem-solving tasks, compared to youth in enhanced care. Conclusion: FFT-HR may delay new mood episodes in symptomatic youth with familial liability to BD. Putative treatment mechanisms include neural adaptations suggestive of improved emotion regulation.
Keywords: mediators